Menjadi manusia kreatif: Sudut pandang psikologi Islami - Fuad Nashori (HUMANITAS: Indonesian Psychological Journal, 2004)
This writing intended to reveal Islamic Psychology view to creativity. Islamic Psychology itself means a study about human soul and behavior based on Islamic world view. Islamic Psychology has a view that religiousness has impact to creativity. Fervent belief, diligent worship, charities and fervent religous experience are proved to enabled man to get creative idea that has higher or more eternal thruth level. Creativity certainly gives impact to the glory of Islamic society.